2004
DOI: 10.1080/00016480310014822
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship between tympanosclerosis and atherosclerosis

Abstract: Our results confirm the reported analogies between tympanosclerosis and atherosclerosis. Although further investigations are needed, promising implications can be predicted for the diagnostic and therapeutic evaluation of this kind of ear patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Inducible nitric oxide synthase is also reported to participate in tympanosclerosis formation 9 19 , 23 Nitric oxide is thought to be secreted (dependent on cytokines) and to reduce osteoclast activity and osteoblast secretion, leading to tympanosclerosis formation 24 …”
Section: Discussionmentioning
confidence: 99%
“…Inducible nitric oxide synthase is also reported to participate in tympanosclerosis formation 9 19 , 23 Nitric oxide is thought to be secreted (dependent on cytokines) and to reduce osteoclast activity and osteoblast secretion, leading to tympanosclerosis formation 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, their control subjects were younger than atherosclerotic patients. Ferri et al investigated the possible relationship between tympanosclerosis and atherosclerosis in 84 patients with significant carotid disease and presented in two publications (9,10). They found that patients with carotid atherosclerosis had higher incidence of tympanosclerosis compared to the controls (38 vs 13%, p=0.05; 36 vs 12%, p=0.005).…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports about the possible relationship between development of tympanosclerosis and atherosclerosis (8)(9)(10). Therefore, in the current study, we aimed a cross-sectional study to examine the relation between tympanosclerosis and angiographic extent and severity of atherosclerosis in patients referred for elective coronary angiography.…”
Section: Introductionmentioning
confidence: 99%
“…atherosclerosis and osteoarthritis) matrix metalloproteinase activity increases 3 . Pathogenetic similarities between atherosclerosis and tympanosclerosis have been described; the pathogenesis of both diseases appears to be related to matrix metalloproteinases 4 . We have previously described a relationship between tympanosclerosis and matrix metalloproteinase 2 (also known as collagenase A), matrix metalloproteinase 9 (also known as collagenase B) and tissue matrix metalloproteinase inhibitor 1.…”
Section: Introductionmentioning
confidence: 98%